Innovation network for micro, small and medium enterprises in Indonesi - Ragil Pardiyono; Yanti Sri Rejeki; Martijanti Martijanti (Decision Science Letters)
This study aims to develop an innovation network model to help MSMEs recover from the downturn due to the pandemic. The basic model used is an innovation network consisting of associations, suppliers, customers and government. The basic model was developed by adding capital and digitalization variables to suit the needs. Data processing uses a structural equation model and the sample is MSMEs in West Java province. This study is the first on the innovation network model for MSMEs affected by the pandemic and the largest number of MSME respondents. The results conclude that according to MSMEs in Indonesia, suppliers, customers, government, associations, capital, and digitalization have an effect on the innovation network. This study concludes that associations, suppliers, customers, government, capital and digitalization all have a positive effect on the innovation network. This finding is the first in the innovation network model for MSMEs that accommodates the needs of the industry to recover from the pandemic situation and adds new literature on industrial innovation networks. While previous studies have a lot of similar literature, all focus on certain types of businesses and on normal economic conditions. This study is different from similar studies because it was conducted on MSMEs in all business sectors and economic conditions in crisis due to the pandemic. These results can be used as a reference in decision making to increase the growth of MSMEs with limited resources.